Stackable keeper using wooden pallet / Shofiyah Zulkifli - Zulkifli, Shofiyah (Faculty of Applied Sciences, 2019)
Furniture is a movable thing which is needed in residents, office or in other locations to support various human activities such as such seating and commonly limited to one single function only. Shortage of material supply for furniture production is one the reason why wooden pallet is one of the alternatives to replace hardwood materials in making furniture. The purposes of this study are to design the Stackable Keeper using wooden pallet (Pinus radiata and produce it at economical price. After design and production process completed, a survey was undertaken to 100 respondents around Bandar Pusat Jengka based on different types of gender, age, and profession. Ten characteristics of the product were evaluated such as about stackable keeper, about wooden pallet, suitable, cheaper, aesthetic, attractive, design, real market, affordable and commercialization. Based on the results, most of respondents of each factors agreed that these kinds of issues such as wooden pallet is cheap and easy to get, colour, following the trend, multipurpose concept, suitability for indoor furniture, space and commercialized in the market meet the customer's satisfaction.